Evaluation of polyacrylamide gel as a substitute for bovine estrual mucus for sperm migration studies in buffaloes - KAUSHAL, GAGANDEEP; PANGAONKAR, G R; CHOUDHARY, K C (The Indian Journal of Animal Reproduction, 2023)
Sperm penetration test was conducted by using different grades of polyacrylamide gel (PAG) i.e. 1 %, 2%, 3% and 4% as penetration media. The effect of duration and temperature of storage of PAG on sperm penetration distance (SPD) was recorded. The 1% and 4% PAG were found to be not suitable for sperm penetration studies, 1% being very thin and 4% being too thick. However, 2% and 3% PAG showed results comparable to fresh oestrual mucus. The mean SPD values in 2% and 3% PAG were 20.5±0.87 and 18.80±0.60 nun/20 min, respectively. The duration and temperature of storage showed no significant effect on SPD values after 60 days in 2% and 3% PAG. It was concluded that 2% or 3% PAG could be used as an alternative medium to evaluate the semen quality of buffalo bulls.